Development of GMP‐1 a molecular chaperone network modulator protecting mitochondrial function and its assessment in fly and mice models of Alzheimer's disease. Issue 7 (27th April 2018) - Pavlov, Pavel F.; Hutter‐Paier, Birgit; Havas, Daniel; Windisch, Manfred; Winblad, Bengt
Abstract: Mitochondrial dysfunction is an early feature of Alzheimer's disease (AD) and may play an important role in the pathogenesis of disease. It has been shown that amyloid beta peptide (Aβ) and amyloid precursor protein (APP) interact with mitochondria contributing to the mitochondrial dysfunction in AD. Prevention of abnormal protein targeting to mitochondria can protect normal mitochondrial function, increase neuronal survival and at the end, ameliorate symptoms of AD and other neurodegenerative disorders. First steps of mitochondrial protein import are coordinated by molecular chaperones Hsp70 and Hsp90 that bind to the newly synthesized mitochondria‐destined proteins and deliver them to the protein import receptors on the surface of organelle. Here, we have described the development of a novel compound named GMP‐1 that disrupts interactions between Hsp70/Hsp90 molecular chaperones and protein import receptor Tom70. GMP‐1 treatment of SH‐SY5Y cells results in decrease in mitochondria‐associated APP and protects SH‐SY5Y cells from toxic effect of Aβ1‐42 exposure. Experiments in drosophila and mice models of AD demonstrated neuroprotective effect of GMP‐1 treatment, improvement in memory and behaviour tests as well as restoration of mitochondrial function.